2014
DOI: 10.3391/ai.2014.9.1.04
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of microfungal “extra oomph” in the invasive red swamp crayfish Procambarus clarkii

Abstract: In the Laurentian Great Lakes, the invasive form of Phragmites australis (common reed) poses a threat to highly productive coastal wetlands and shorelines by forming impenetrable stands that outcompete native plants. Large, dominant stands can derail efforts to restore wetland ecosystems degraded by other stressors. To be proactive, landscape-level management of Phragmites requires information on the current spatial distribution of the species and a characterization of areas suitable for future colonization. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We found that many of these taxa are directly linked to crayfish as a specialized host, and others that are likely associated with crayfish due to shared habitat requirements. Our highest ranked candidate bioindicators, with rank values of 6 ( Cynobium sp., Aspergillus flavus , and Talaromyces helicus ) were previously identified as key associated taxa in invasive P. clarkii or C. chelax in Italy and Australia (Dörr et al, 2012; Foysal et al, 2019; Garzoli et al, 2014). In our study, out of 1003 total eDNA samples from across the state of California (Meyer et al, 2021), Cynobium sp .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that many of these taxa are directly linked to crayfish as a specialized host, and others that are likely associated with crayfish due to shared habitat requirements. Our highest ranked candidate bioindicators, with rank values of 6 ( Cynobium sp., Aspergillus flavus , and Talaromyces helicus ) were previously identified as key associated taxa in invasive P. clarkii or C. chelax in Italy and Australia (Dörr et al, 2012; Foysal et al, 2019; Garzoli et al, 2014). In our study, out of 1003 total eDNA samples from across the state of California (Meyer et al, 2021), Cynobium sp .…”
Section: Discussionmentioning
confidence: 99%
“…Stagnospora sp ., Liu et al, 2012; Ramimonilia apicalis , Ricks and Koide, 2019). Garzoli et al (2014) suggested that these and other fungal species are common in the crayfish gut to help break down plant detritus; a primary source of food for P. clarkii , and thus are likely to be tightly associated with P. clarkii . Overall, 4 out of 9 candidate bioindicator taxa were fungal species in the Phylum Ascomycota.…”
Section: Discussionmentioning
confidence: 99%
“…In other freshwater systems throughout Europe this species has been found to drastically reduce the biomass and survival of establishing macrophytes (van der Wal et al, 2013) and macroinvertebrates (Garcia et al, 2015). While other recent research in Italy has found that some microfungal flora species living in its gut are potential phytopathogenic, making P. clarkii a potential vector of plant diseases (Garzoli et al, 2014), further increasing the risk to local biodiversity especially in an ecologically important Tree Protected Area, such as at Fiddien Valley (Government Notice 473, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Red swamp crayfish make burrows in the pond and cause a noticeable physical impact on freshwater ecosystems (Barbaresi, Tricarico & Gherardi ; Scalera & Zaghi ; Scalici et al . ; Garzoli, Paganelli, Rodolfi, Savini, Moretto, Occhipinti‐Ambrogi & Picco ). Some marine alien or lessepsian fish species belonging to Tetraodontids such as Sphoeroides pachygaster and Lagocephalus sceleratus are known for their toxicity due to the neurotoxin tetrodotoxin that may produce paralysis of the diaphragm and death (Andaloro et al .…”
Section: Impact Of Aquatic Alien Speciesmentioning
confidence: 99%
“…Containment strategies have been proposed for red swamp crayfish control (Garzoli et al . ), and two LIFE projects have been recently funded for this purpose: RARITY (http://www.life-rarity.eu/pages/rarity_en.htm) and SOS TUSCAN WETLANDS (http://www.life-sostuscanwetlands.eu/index.php/it/?lang=en). The management of alien salmonids is completely different from the above‐mentioned species, and some of these naturalized species are important for local freshwater fishery and consequently worth of conservation and protection.…”
Section: Management Of Alien Species: Status and Perspectivementioning
confidence: 99%